Diálogos sobre a alfabetização, a leitura e a escrita no programa Provinha Brasil - Endlich, Ana Paula Rocha (2014)
This documentary research analyzes the literacy, reading and writing conceptions underlying to the test called Provinha Brasil in the period of 2008-2012 and the outlook wherein this assessment program is produced. It is based on the bakhtinians referential and Gontijo’s (2008, 2013) literacy concept. By using the Provinha as a discourse gender, it discusses the previous links within the production context of this evaluation, the Program authorship and their main recipients. It notes that Provinha is created as a response to the demands of literacy evaluations coming from international organizations, such as, the World Bank and the United Nation Organization for Education (UNESCO). The assessment is elaborated by the National Institute of Studies and Research named Anísio Teixeira (Inep) as the organ in charge of coordinating the evaluations in the Country, along with the collaboration of the university researchers and the civil society organizations in order to show scientific reliability allied to the democratic participation in the production process. The main recipients are the Department of Education managers and Teachers. The first ones are responsible for joining the evaluation program and taking administrative measures for the operationalization in the networks. The Teachers have the central role to follow the material orientations and reorganize its practice according to the improvements of the children’s performance in the test. On the other hand, those are not considered as subjects of sayings and a homogenizer speech on the development is legitimated. From the tests carried out and reference matrices and their axles, the research analyzes how the theoretical differentiation among literacy is concretized in the organization of the tests. Literacy, seen as an appropriation of the writing system, is evaluated in the first axle of the test mainly as identification of smaller units of language, such as, letters, syllables and phonemes. The reading skills connected to the literacy as designed in the program assumptions, are sometimes measured as the decoding of decontextualized words and sentences, also as the capture of the text predetermined meanings. Writing is only evaluated in year of 2008 and through items that requested a coding of words and sentences dictated by the test applicator. This way, Provinha Brasil contributes for the subtraction of political and transformer potentialities of the mother tongue learning in the Country.